Biomechanical Analysis of T-Kick in Pencak Silat Athletes in Tapak Suci, South Bengkulu - Andika Prabowo (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The aim of this research is to find out whether the T kick technique at Tapak Suci South Bengkulu school is good or still needs more practice in improving the T kick. The research method used in this research is a qualitative descriptive method. The population at Tapak Suci College, South Bengkulu and used in this research was approximately 50 athletes. And the samples used in this T-kick biomechanics analysis research were 20 athletes. The data collection technique used in this research is test and documentation, where the tests carried out are then adjusted to suitability indicators for T kicks and the documentation taken is in the form of an analysis process through the kinovea application. The results of this research are that the overall T kick ability of South Bengkulu Tapak Suci fighters from the first phase to the last phase, has different abilities, by looking at the suitability of the T kick movement, starting from phase one or the initial stance of all athletes who perform the T kick. a score of 64% and falls into the fair category, the second phase is 72% good, while the third phase gets a score of 72% good, the fourth phase gets a score of 64% fair and the last phase is the final phase of the kick and gets a score of 77% good, if calculated correctly Overall, the average obtained is 70% (sufficient)